Perfil nutricional de atletas de jiu-jitsu: uma revisão sistemática - Lima, Bruno de Castro (Brasil, 2024)
Introduction: Jiu-jitsu is expanding on the world stage, over the years the search for the modality in gyms and fight training centers has been routine by art enthusiasts, as the modality promotes benefits to physical, mental and well-being. be with those who practice it. In competitive jiu-jitsu, athletes need to adapt to their category, which is divided by weight, aiming for balance in combat. The intake of carbohydrates and proteins are essential in the life of an athlete, many athletes undergo radical diets to fit into their category, such strategies can lead to several physiological and psychological changes, there is partial knowledge among jiu-jitsu athletes regarding what refers to healthy eating and the consumption of supplements. Objectives: Analyze studies related to the nutritional profile of jiu-jitsu athletes, and investigate whether these athletes are within the recommendations. Methodology: A literature review was carried out through searches in the databases Google Scholar, Pubmed, Digital Library of Theses and Dissertations etc. The inclusion criteria were studies that presented the nutritional profile of adult jiu-jitsu athletes of both sexes. Results: 18 articles were found, 3 were excluded for being duplicates, 7 were included for full reading, and only 3 articles were selected for review. Conclusion: Jiu-jitsu athletes have a low consumption of carbohydrates, an inadequate intake of vitamins C, A and B5, and a low consumption of important minerals such as calcium, magnesium, iron, potassium and sodium.